The Effect of (Vertimax) Exercises on the Molecular Pressure of Oxygen, the Explosive Ability of the Two Legs, and the Accuracy of Scoring for Advanced Football Players - Bashar Abbood Fadel 1 , A. Muhsin Muhammed Hassan 1 , Ali Sadiq Shaker 1 , Sura Irahim Luabi 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aimed to: Prepare (Vertimax) exercises for football players. Learn about the effect of exercises(Vertimax) on the molecular pressure of oxygen and the explosive ability of the two men, as well as the skill ofscoring accuracy for advanced soccer players. This study examined several axes, including the introductionto the research and its importance, which lies in the use of exercises (Vertimax), as the importance ofresearch lies in preparing these exercises through working with extreme intensity exercises and sufficientrest periods, as these exercises work to develop the molecular pressure of oxygen and the explosive capacityof the two legs. For advanced soccer players, in addition to developing the scoring skill of advanced soccerplayers, as these exercises give the best possible opportunity to achieve the greatest gains in the ability tojump, speed and explode in order to target the central nervous system (CNS) and activate all movementmodes and make them circulate To better and also improve the player’s ability to perform the scoring skillbetter throughout the match time and thus the player’s performance is reflected in the team’s result.